The Devil's backbone [videorecording (DVD)] - Toro, Guillermo del, 1964-; Toro, Guillermo del, 1964-; Paredes, Marisa, 1946-; Noriega, Eduardo, 1973-; Tielve, Fernando (Criterion collection, 2013)
When twelve-year-old orphan Carlos arrives at the Santa Lucia School, he discovers dark secrets and the restless ghost of a murdered student.